Dual-Mode Multicolor Display Based on Structural and Fluorescent Color CdS Photonic Crystal Hydrogel - Liu, Zihan (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this study, we prepared a multicolor structural-fluorescent CdS-PEGDA photonic crystal hydrogel (SFC-CPH) with a dual display mode, which has two different optical states: structural color mode and fluorescent color mode. SFC-CPH displays structural color mode under visible light and fluorescent color mode under ultraviolet light. Initially, monodisperse CdS colloidal particles were synthesized via a hydrothermal method, leading to the self-assembly of a photonic crystal template. The high refractive index of CdS contributes to the photonic crystals' low-angle dependence and vivid structural colors. Then, a variety of fluorescent molecules were doped into poly(ethylene glycol) diacrylate (PEGDA) hydrogel and combined with photonic crystals with distinct structural colors to prepare three distinct colors of SFC-CPH. We also investigated the optical characteristics and surface properties of these photonic crystal hydrogels. Based on these dual-mode display characteristics, we designed several dual-mode display patterns and a method for information encoding. The unique property of this photonic crystal hydrogel material suggests its substantial potential for applications in information storage, security, and encoding, offering innovative avenues in the realm of information display